2012
DOI: 10.3402/dfa.v3i0.19178
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of diabetic smokers and non-smokers who undergo lower extremity amputation: a retrospective review of 112 patients

Abstract: BackgroundA diabetic foot or lower extremity amputation may be exacerbated by or related to the smoking habits and history of the patient.Patients and methodsOf the 112 diabetic patients in this retrospective study, 46 were non-smokers and 66 were smokers. The smokers were further categorized into patients who: 1) did not cease smoking; 2) ceased in the immediate post-operative period but resumed within 3 months; and 3) ceased up to and at the 3-month post-operative period. The patients were also divided by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Smoking persons with diabetes have more proximal amputations. 30 Part of the explanation to differences in outcomes is likely to be worse hyperglycaemia and higher prevalence of smoking in the lower SEP groups.…”
Section: Strengths and Weaknesses In Relation To Other Studies Discumentioning
confidence: 99%
“…Smoking persons with diabetes have more proximal amputations. 30 Part of the explanation to differences in outcomes is likely to be worse hyperglycaemia and higher prevalence of smoking in the lower SEP groups.…”
Section: Strengths and Weaknesses In Relation To Other Studies Discumentioning
confidence: 99%
“…There have been several studies that revealed the relationship between smoking tobacco status and lower limb amputations (Anderson et al 2012;Lin et al 2020). In our study, smoking tobacco was statistically significant as a risk factor for major amputation in the univariate analysis and >30 pack/year remained statistically significant in the multivariate analysis (p=0.011, HR=1.931).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cigarettes has been shown to delay wound healing [28,29] and diabetic patients with foot ulcers who smoke are more likely to require amputation than non-smokers [30]. In RA patients smoking cigarettes has been linked with increased disease activity [31][32][33] and the development of rheumatoid nodules [34].…”
Section: Methodsmentioning
confidence: 99%